Drunken Master - Lau Kar Leung; Cheung, Tony ca. 20. Jh; Ch'eng, Lung 1954-; Lau, Andy 1961-; Mui, Anita 1963-2003 (Splendid Film, 2002)
This sequel to one of Jackie Chan's first hit movies was made at a time when the Chinese folk hero Wong Fei Hung had been played to death. Somehow though, it still manages to offer up a fresh take on the character as well as recapturing a little of that old school magic. The story finds the "young" Fei Hung (Chan) uncovering a plot to smuggle Chinese antiques out of a local foundry. Unfortunately, Fei Hung is unable to step in as he has been forbidden to drink by his father (Ti Lung). Now he is forced to choose between disobeying his family or stopping a group of disrespectful foreigners. Despite some slightly incoherent plot points, mainly due to "creative differences" between Chan and director Liu Chia-Liang, "Drunken Master 2" is a superb return to the classic kung fu movie formula. Not only does it recreate the period and atmosphere perfectly, but it also recalls a lot of those light-hearted scenarios that we all know and love so well. However, the big highlight here is undoubtedly the action as "Drunken Master 2" contains some of the finest fights ever committed to celluloid. [www.fareastfilms.com]